Salivary caries parameters: Comparative study among Yemeni khat chewers and nonchewers - Al-Alimi, K.R.; Razak, A.A.A.; Saub, R. (Elsevier Taiwan, 2014)
Background/purpose: Millions of people in Yemen and East African countries chew khat for more than 5 hours daily for its amphetamine-like effects. Previous studies have associated khat chewing with salivary glands enlargement, inflammation, and xerostomia. However, no information is available on the possible effects of this habit on salivary parameters. This comparative study aims to evaluate salivary parameters, such as salivary flow rate, pH, and viscosity among Yemeni khat chewers and nonchewers. Materials and methods: Stimulated saliva was collected from 30 Yemeni male khat chewers and 30 nonchewers living in Sana'a City. Salivary flow rate, pH, and viscosity were measured. Data were analyzed using the Mann-Whitney test, an independent t test and the Chi-square test. Results: The mean salivary flow rates (mL/minute) among khat chewers and nonchewers were 0.71 +/- 0.07 mL/minute and 0.99 +/- 0.09 mL/minute, respectively. The independent t test showed a significant difference in salivary flow rate between the two groups at (P < 0.05). The mean pH values among khat chewers and nonchewers were 6.32 +/- 0.44 and 6.78 +/- 0.35, respectively. The Mann-Whitney test showed that khat chewers have significantly lower salivary pH compared to nonchewers at (P < 0.05). The salivary viscosity of khat chewers and nonchewers also differed significantly at (P < 0.05). Conclusion: The findings suggest that khat-chewing habits may reduce salivary flow rate, lower salivary pH, and lead to unhealthy viscosity. Copyright (C) 2014, Association for Dental Sciences of the Republic of China. Published by Elsevier Taiwan LLC. All rights reserved.